The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2298/yjor130217035j
|View full text |Cite
|
Sign up to set email alerts
|

Optimal pricing and promotional effort control policies for a new product growth in segmented market

Abstract: Market segmentation enables the marketers to understand and serve the customers more effectively thereby improving company’s competitive position. In this paper, we study the impact of price and promotion efforts on evolution of sales intensity in segmented market to obtain the optimal price and promotion effort policies. Evolution of sales rate for each segment is developed under the assumption that marketer may choose both differentiated as well as mass market promotion effort to influence the uncaptured mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Further, Jha at al. [21] have analyzed the impact of price and promotional efforts on the evolution of sales intensity in the segmented market.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Jha at al. [21] have analyzed the impact of price and promotional efforts on the evolution of sales intensity in the segmented market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On integrating the equations (20) and (21) and by utilizing the transversality condition, we get the optimal values of costate variables:…”
Section: Optimality Necessary Conditionsmentioning
confidence: 99%
“…From the perspective of new product pricing and promotion decision-making research, domestic and foreign research mainly focuses on two aspects. First, research on the optimal pricing and promotion strategies of new products when there are different market segments [8][9][10][11] studied the decision-making of pricing and promotion efforts in a multistage supply chain. Liu et al [12] studied the impact of promotion efforts under dual channels on the profits of manufacturers and retailers and concluded that only synergy between the upstream and downstream of the supply chain can improve promotion efficiency.…”
Section: Introductionmentioning
confidence: 99%